Living thought and living things On Roberto Esposito’s "Il pensiero vivente" - Franchi, Stefano (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
The essay discusses Roberto Esposito’s claim that Italian thought and the Italian tradition offer philosophy a way out of the dire situation it has fallen into as a consequence of the linguistic turn it took at the beginning of the 20th century. According to Esposito, Italian thought is animated by a genealogical vocation generating political, historical, and life paradigms that may revive philosophy’s universal ambitions against its current linguistic relativism. The essay discusses this claim in light of the tension between ontology and history that Esposito himself raises. It concludes that the opportunities opened up by Italy’s “genealogical vocation” should be supplemented by a philosophy of history that is currently lacking from Esposito’s account.